High Power Efficiency Buck Converter Design for Standalone Wind Generation System - Yigeng Huangfu; Ruiqing Ma; Bo Liang; Yuren Li (International Journal of Antennas and Propagation)
In wind generation system, the power converter efficiency is one of the key factors for the performance of the system. In those systems, DC/DC Buck converter is widely used for high power system. Considering the converter’s cost and efficiency, this paper mainly focuses on the design of an improved topology Buck converter adopted for high power standalone wind generation system. The designed converter uses multi-MOSFETs in parallel instead of the IGBTs, in order to increase the conductive current as well as the converter switch frequency. From the experimental tests results, the maximum efficiency of the designed 2 kW Buck converter is up to 96% based on maximum power point tracking (MPPT) method.